(untitled) (Research, Society and Development, 2020)
The change in the perspective of integration towards an inclusive education takes place from the recognition of education as a right of all established by the Federal Constitution of 1988. However, although guaranteed by law, the inclusion of students with disabilities is still a challenge. This article sought to discuss some ways to make this inclusion effective. For this, we highlight the importance of the knowledge of two regulatory frameworks related to inclusive policy by school agents: the Guatemala Convention (1999) and the Brazilian Law of Inclusion (LBI/2015). In the first moment a brief history of the school inclusion policy is made and the importance of the Guatemala Convention and the Brazilian Inclusion Law in the inclusive educational legislation in Brazil; we discuss the role of the pedagogical coordinator as mobilizing agent and articulator of inclusive pedagogical practices in the school and we propose actions for the implementation of the inclusion in the school environment. The study was elaborated from important and recent theoretical productions of researchers that study this theme. The research is bibliographic and documental with qualitative approach. To support the research we use books, academic articles, legislation and dissertations about the school inclusion of the person with disability. From the study carried out, we can conclude that inclusion requires from the knowledge of legal provisions to the implementation of inclusive educational practices in order to eliminate the distance between laws and actions in the teaching process.